Total export and economic growth :evidence in Asean - 3 - Royston Andy, Tony (Universiti Malaysia Sarawak (UNIMAS), 2007)
The objective of this study is to reveal causality pattern between total export and economic growth which is represent by Gross Domestic Product (GDP)in ASEAN-3 countries, namely Malaysia, Thailand and Indonesia, and hence determine the validity of the export- led growth hypothesis in those countries. The data used are from period 1970 to 2005 and was transform in logarithmic form. From the test conducted, the result brings to a few conclusions. A cointegrated relationship between export and economic growth was not detected in all the countries.This means,there is no long run relationship between GDP and total exports and can be said that the variables are drift apart in the long run.Moreover, further analysis showed that there is a bi-directional causality pattern exists in ASEAN-3 countries. Export is found as Granger cause GDP and GDP is found as Granger cause export as well. Government policies towards outward-oriented is welcome to propel economic growth as well as exports.